Chain-specific antibodies for laminin-511. (December 2013) - Zamurs, Laura; Pouliot, Normand; Kusuma, Nicole; Nice, Edouard C.; Burgess, Antony W.
Abstract Mouse monoclonal antibodies (mAbs) that bind to specific chains of laminin-511 (LM-511) have been developed. Antibody 2F12 binds to the LMα5 chain, 3G10 binds to the LMβ1 chain and 3C12 binds to the LMγ1 chain. These antibodies can be used to purify LM-511, to detect LM-511 in cell extracts or to detect the location of LM-511 in tissue by immunohistochemistry. In combination, the antibodies recognize all three chains of LM-511 and combinations of the antibodies can be used to quantitate levels of LM-511 in physiological fluids. One of the antibodies (3G10) is a potent inhibitor of the activity of LM-511 in cell adhesion, spreading and proliferation assays.